The bounded approximation property of variable Lebesgue spaces and nuclearity - Delgado, Julio; Ruzhansky, Michael (MATHEMATICA SCANDINAVICA, 2018)
In this paper we prove the bounded approximation property for variable exponent Lebesgue spaces, study the concept of nuclearity on such spaces and apply it to trace formulae such as the Grothendieck-Lidskii formula. We apply the obtained results to derive criteria for nuclearity and trace formulae for periodic operators on R^n in terms of global symbols.